Uporaba stolpčnih diagramov pri pouku fizike - Vidmar, Monika (Matrika, 2018)
The use of multiple representations in physics learning leads to a better problem solving and understanding of physical concepts. This article is focused on bar charts and the way they can be used in different physics topics.
Keywords: bar charts; conservation laws; delo; energija; energy; fizikalni problemi; ohranitveni zakoni; physics teaching; poučevanje fizike; problem solving; stolpčni diagrami; work